O papel da propriedade intelectual e os direitos autorais na proteção das criações da moda - Suzano, Maria Eduarda Alves (2024)
This final paper aims to observe how fashion designs are protected by the brazilians Industrial Property Law and the Copyright Law, in order to understand whether there is a need for legislative reforms or the creation of new, more effective legislation to protect fashion creations. This is because, as the fashion scene grows, more litigation arises on the subject, mainly involving violations of the Industrial Property Law and the Copyright Law. In Brazil, unlike other countries in Europe and the United States, it does not have specific legislation or an area of law aimed at fashion creations, therefore, seeking existing legislative support, such as the laws mentioned above. In this sense, cases such as Hermès versus Village 284, Jouer Couture versus Shein and Yves Saint Laurent versus Louboutin are analyzed, since they all demonstrate the possibility of fashion creations being protected by existent laws, even if such protection is not expressed in them